Developing a University Extension Programs Gateway Services Information System: A Baseline Survey - Ryan F. Arago (Universidade Estadual de Alagoas, 2023)
Universities are increasingly adopting and engaging in social responsibility awareness activities. University Social Responsibility (Hollister, R. 2016) are manifested in universities through implementing extension programs that enable them to associate with different beneficiaries. With the help of technology, people are able to access enormous amounts of information in a more convenient way. Thus, the use of technology would be able to address the need for social responses of the university to be more effective. The main objective of the study is to develop a system gateway for universities, beneficiaries, and sponsors of extension services.  The research design used in the study is quasi-experimental design. The proponent conducted this study among the faculty members of Quezon City University totalling to 50 respondents. Whereas the proponent applied the Agile Development Model in building the prototype of the Gateway Services Information System, and used PHP and MySQL to develop the software. Based on the findings, the study concluded that: the respondents agreed that the continuous engagement of social responsibility programs provide a positive impact on both the university and the beneficiaries, and recommended that such usage of a gateway system will bring more ease and effectively of the process, resulting to a more positive impact. Overall, the respondents find the extension programs as effective. The findings suggest that respondents perceive capability training program, community outreach program, and high-impact, long-term integrated community-based development program as effective for the beneficiary, and it is recommended that such programs should be expanded to a more sets of program options and types. The respondents also agreed that strategies in implementing extension service programs are successful, and it is suggested that the gateway information system should have a more complex communication capable of catering such preparation activities for implementation. The respondents also strongly agreed that the key factors are critical and important for sustainability and is recommended that such complex planning and management of an extension program should be catered by the system. Overall, the assessment of the respondents agreed that the gateway software is capable of addressing the needs of both universities and beneficiaries, and it is recommended that the gateway information system will be accessible to all possible educational institutions which seek to give aid to beneficiaries.